EFFICIENCY OF TAX ADMINISTRATION IN THE SYSTEM OF ECONOMIC SECURITY IN KYRGYZSTAN - Karybaeva Ch. S. (Vestnik Issyk-Kulʹskogo universiteta, 2025)
The role of taxes as a factor of economic security depends on the specific situation, peculiarities - the development of the country, which it is experiencing, the nature of the economic policy pursued, the stability of state power. The tax system, acting simultaneously as a factor of economic security, should contribute to ensuring such development of the economy, which would create the necessary financial conditions for socio-economic stability and development of the state and each region, preserving the integrity and unity of the financial system (including monetary, budgetary, credit, tax and currency systems), successfully countering internal and external threats to Kyrgyzstan and its regions In modern economic conditions any state pays special attention to such phenomena as tax evasion, because they have a negative and sometimes threatening impact on the economy, significantly affect the state of economic and national security of the state. The tax component of economic security, its role and importance in the conditions of modern economy are becoming particularly relevant. This is due to the large number of violations in the field of taxation, arrears of tax payments to budgets of all levels, as well as the presence of a significant amount of the shadow sector of the economy. These circumstances represent a significant problem for the state both from the point of view of ensuring and strengthening tax security, and from the point of view of economic stability of the state as a whole. The most important element of economic security of the country in modern conditions is tax security. Taxation is a link between the economy and the budget system, which redistributes funds between economic entities, individuals and the state.